2017
DOI: 10.1063/1.5005946
|View full text |Cite
|
Sign up to set email alerts
|

Triplet and beam interaction in a plasma

Abstract: The interaction of three waves requires wavelength and frequency matching conditions. Without the presence of a particle beam, if the conditions are satisfied and if the frequency of the envelope is lower than the lowest frequency of the waves, they exchange energy and the evolution of the envelope of each wave is given by a constant plus a sinusoidal function. On the other hand, if a particle beam propagates within electrostatic and electromagnetic fields with no wavelength and frequency match, the energy exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As seen in Ref. 16, the regular dynamics of the envelopes is completely destroyed by the interaction: the longitudinal mode is excited, growing exponentially. After saturation, the amplitude of the longitudinal mode begins to oscillate around a mean value with two characteristic frequencies: the highest one is related to the frequency of the plasma, while the lowest one is related to the frequency of the triplet (in the case of no particles).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…As seen in Ref. 16, the regular dynamics of the envelopes is completely destroyed by the interaction: the longitudinal mode is excited, growing exponentially. After saturation, the amplitude of the longitudinal mode begins to oscillate around a mean value with two characteristic frequencies: the highest one is related to the frequency of the plasma, while the lowest one is related to the frequency of the triplet (in the case of no particles).…”
Section: Introductionmentioning
confidence: 83%
“…In a previous work, 16 it was shown that when an initially cold beam, even for a very small charge, is allowed to interact with a triplet, the dynamics of the system is completely changed. Besides the triplet interaction, the particles interact with the waves and with themselves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations